Respuesta :
Answer:
Multiply the second equation by −2 to get −8x − 6y = −30.
Step-by-step explanation:
{2x + 6y = 12
{4x + 3y = 15
{2x + 6y = 12
{−8x − 6y = −30 >> New Equation
* Doing this will give you additive inverses of −6y and 6y, which result in 0, so they are both ELIMINATED.
** [3, 1] is your solution.
I am joyous to assist you anytime.
Multiply the second equation by −2 to get −8x − 6y = −30 and this can be determined by carefully observing both the equations.
Given :
System of equations: 2x + 6y = 12 ; 4x + 3y = 15
The following steps can be used to evaluate which action creates an equivalent system that will eliminate one variable when they are combined:
Step 1 - Write the system of equations.
2x + 6y = 12 --- (1)
4x + 3y = 15 --- (2)
Step 2 - Now, multiply -2 in equation (2).
(4x + 3y = 15) [tex]\times[/tex] -2
Step 3 - Further simplify the above equation.
-8x - 6y = -30 --- (3)
Step 4 - Now, add equation (1) and equation (3).
2x + 6y - 8x - 6y = 12 - 30
-6x = -18
x = 3
From the above steps, it can be concluded that the correct option is A) Multiply the second equation by −2 to get −8x − 6y = −30.
For more information, refer to the link given below:
https://brainly.com/question/2263981